DNA cross-triggered cascading self-amplification artificial biochemical circuit. Issue 2 (26th November 2014) - Nie, Ji; Zhao, Ming-Zhe; Xie, Wen Jun; Cai, Liang-Yuan; Zhou, Ying-Lin; Zhang, Xin-Xiang
Abstract : A novel DNA cross-triggered cascading self-amplification artificial biochemical circuit can be triggered by either of two fully independent oligonucleotide factors (∼2 amol) and amplify both of them by 10 5 –10 7 fold. Abstract : The construction of compact and robust artificial biochemical circuits based on nucleic acids can help researchers to understand the essential mechanisms of complex biological systems, and design sophisticated strategies for various requirements. In this study, a novel DNA cross-triggered cascading self-amplification artificial biochemical circuit was developed. Once triggered by trace amounts (as low as 2 amol) of either of two fully independent oligonucleotide factors under homogeneous isothermal conditions, the circuit simultaneously amplified both factors by 10 5 –10 7 fold, which was proved using mass spectrometry. The compact and robust circuit was successfully used to construct a multi-input Boolean logic operation and a sensitive DNA biosensor based on the dual-amplification of both the target and reporter. The circuit showed great potential for signal gain in complicated molecular programming, and flexible control of nucleic acid nanomachines in biochemical network systems and nanotechnology.